2022
DOI: 10.3390/biomedicines10061388
|View full text |Cite
|
Sign up to set email alerts
|

Thixotropic Red Microalgae Sulfated Polysaccharide-Peptide Composite Hydrogels as Scaffolds for Tissue Engineering

Abstract: Sulfated polysaccharides of red marine microalgae have recently gained much attention for biomedical applications due to their anti-inflammatory and antioxidant properties. However, their low mechanical properties limit their use in tissue engineering. Herein, to enhance the mechanical properties of the sulfated polysaccharide produced by the red marine microalga, Porphyridium sp. (PS), it was integrated with the fluorenylmethoxycarbonyl diphenylalanine (FmocFF) peptide hydrogelator. Transparent, stable hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The existence of a strong matrix, with a prominent viscoelastic nature, is also confirmed by the loss tangent (tanδ = G ′′ /G ′ ) value, which is 0.0526 for Fmoc-FFK/Fmoc-FF (1/20, w/w). This increase in the mechanical features, which are well documented for other multicomponent matrices, seems to be related to the ability of the Fmoc-FF building block to govern and drive the gelation process, reducing the probable electrostatic repulsion in pure Fmoc-FFK gels [46]. These electrostatic repulsions may justify the low mechanical response of Fmoc-FFK hydrogels, as evidenced by the lower G ′ values for multicomponent matrices with respect to the Fmoc-FF one (G ′ = 23,160 Pa at 1.0 wt% and 1.0 Hz; rheological characterization reported in Figure S10).…”
Section: Rheological Characterizationmentioning
confidence: 57%
“…The existence of a strong matrix, with a prominent viscoelastic nature, is also confirmed by the loss tangent (tanδ = G ′′ /G ′ ) value, which is 0.0526 for Fmoc-FFK/Fmoc-FF (1/20, w/w). This increase in the mechanical features, which are well documented for other multicomponent matrices, seems to be related to the ability of the Fmoc-FF building block to govern and drive the gelation process, reducing the probable electrostatic repulsion in pure Fmoc-FFK gels [46]. These electrostatic repulsions may justify the low mechanical response of Fmoc-FFK hydrogels, as evidenced by the lower G ′ values for multicomponent matrices with respect to the Fmoc-FF one (G ′ = 23,160 Pa at 1.0 wt% and 1.0 Hz; rheological characterization reported in Figure S10).…”
Section: Rheological Characterizationmentioning
confidence: 57%
“…In addition, it has been reported that these polysaccharides did not present cytotoxicity, and they can keep low glycemic levels and exert antioxidant activity simultaneously [7]. Microalgae sulfated polysaccharides have also gained attention for biomedical applications, such as developing tissue engineering scaffolds [8]. Microalgae sulfated polysaccharides have also been considered promising candidates in other sectors, such as the food industry and agriculture [9].…”
Section: Introductionmentioning
confidence: 99%